"It exists": An exploratory study of treatment experiences in men with eating disorders. (6th January 2020) - Thapliyal, Priyanka; Conti, Janet; Bandara, Ranidu S. L.; Hay, Phillipa
Abstract: Objective: Eating disorders (EDs) in men are often overlooked although they are associated with similar comorbidities and health issues as found in women. The present study is an in‐depth analysis of treatment experiences of eight men who had sought help, were diagnosed with an ED and received ED‐specific treatment. Method: Data were generated from an open‐ended interview that explored men's narratives of their experiences of an ED, as well as questions that focused on their help‐seeking behaviours and treatment experiences. Interviews were transcribed and thematically analysed. Results: This analysis resulted in four themes. The first theme focused on how men ascribed meaning to the ED experience and how these negotiations shaped their help seeking behaviour. The second theme focused on some of the barriers and expectations of men that they encountered when negotiating treatment for an ED. The third theme encompassed the experiences of men when they received the ED‐specific treatment. The last theme included the positive outcomes of treatment and role of health professionals in treating EDs in men. Conclusion: The findings highlight the importance of person‐centred ED treatments for men. Also identified was a need for improved health literacy among health practitioners in the field of EDs, specifically an increased awareness of the development of tailored interventions for men.